Heart of darkness. - Bastiaans, Christiaan; Brouwer, Marianne; Chen, Zhen; Diserens, Corinne; Elliott, David; Godard, Jean-Luc; Guidieri, Remo; Hou, Hanrou; Huang Yong Ping; Ishaghpour, Youssef; Peyzdjou, Chohreh; Said, Edward; et al. (Otterlo : Kröller-Müller Museum, 1997)
Barbier, Dominik ; Bastiaans, Christiaan ; Biefer/Zgraggen ; Birnbaum, Dara ; Borland, Christine ; Cai Guo-Qiang ; Chen Zhen ; D'Orazio, Federico ; Faber, Mindy ; Fagin, Steve ; Feyzdjou, Chohreh ; Fusco, Coco ; Gibbons, Joe ; Godard, Jean-Luc ; Gomez-Pena, Guillermo ; Hatoum, Mona ; Heredia, Paula ; Hill, Gary ; Huang Yong Ping ; Marker, Chris ; Oursler, Tony ; Ruiz, Raoul ; Samore, Sam ; Signer, Roman ; Smith, Michael ; Sterbak, Jana ; Tajiri, Rea ; Tanaka, Janice ; torre, Ed de la ; Totten, Melissa ; Ward, Nari ; Wenda, Gu ; Yonemoto, Bruce ; Zakharov, Vadim
Heart of darkness, Kröller-Müller Museum, Otterlo, December 18, 1994 - March 27, 1995
biografie, videografie
Engels
boek